Effect of fruit and vegetable blanching and compression on the loss of multilayer chips - Dudarev, Igor; Panasyuk, Svitlana; Taraymovich, Iryna; Say, Volodymyr (Kyiv : INMATEH, 2021)
Chips are a useful and popular product that is produced in most countries of the world. The main processes of traditional chips technology are slicing fruits and vegetables into thin slices, blanching and drying slices. Multilayer chips are formed from several layers of different materials (fruits, vegetables and seeds). For forming of such chips, it is important that the layers of different materials stick together well. Studies have shown that the material type and blanching time significantly affect the adhesion of material and loss of chips. Also, effect of compression of raw material layers on the chips loss was studied.
Keywords: fruit chips; vegetable chips; blanching time; chips loss; chips technology